KNOWLEDGE AND ATTITUDE OF RURAL WOMEN WEAVERS TOWARDS SOCIAL MEDIA MARKETING - DEEKSHITA DUTTA and T. RADHA, (The Journal of Research ANGRAU, 2022)
The objective of this research is to find out the level of knowledge of50 women weavers onsocial media marketing and their attitude towards the same.The study was conducted in the state ofAssam between August and September, 2021 and the district Lakhimpur was selected as the studyarea.Two villages were selected randomly and a sample of 25 weavers were selected from eachvillage,thus, the making total sample size of 50. The main findings of the study revealed that morethan half (60%) of the respondents has medium level knowledge on social media marketing and itssites and 40% have unfavourable attitude towards it. However, it is also worth mentioning that nearlyequal number of respondents (38%) have favourable attitude. The women weaved different types offabrics like cotton and silk and some of the noteworthy garments are the traditional mekhe lachadarof Assam and Gamusa.